Sociodemographic profile of adolescents deprived of their liberty in the interior of the state of São Paulo - Penacci, Fernanda Augusta [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Barbosa, Guilherme Côrrea [UNESP] (My University, 2019)
Objective: Describe the sociodemographic profile of the adolescent female population deprived of liberty in the interior of the State of São Paulo. Methods: Compedium of a PhD thesis in collective health, whose cross-sectional study was carried out with secondary data in the two Centers for Socio-educational Assistance for Women in the city of Cerqueira César, State of São Paulo. 374 adolescents were analyzed in the age group from 12 to 21 years old of age, from January 2015 to February 2016. A description of the population was performed by means of summary measures: median, minimum and maximum and percentage estimates. For statistical analysis SPSS® software version 21.0 was used. Results: The adolescent’s mean age was 17 years old, with the predominance of brown skin color. It was observed that 69.8% of the adolescents have elementary education and school dropout was 92%. Few adolescents were employed (21.4%) before entering the Foundation and most of them had passages through the Guardianship Council (64.7%). The average family member is of four people; 53% of them live with their parents and 31.4% have a stable union. The average family income was R $ 1,576.00. The Regional Network for Health Care 12 concentrates the majority of adolescents. Conclusion: There is a demand for speed of the public policies and cohesion with the needs of the female population, associated with the affirmation that the programs for the adolescent’s care, in general, keep them distant and passive of their notions of health, education, personal and social development.
Perfil sociodemográfico de adolescentes privadas de liberdade no interior do estado de São Paulo
Keywords: Adolescent; Institutionalized adolescents; Public health